Determining the Correlation of Fat-Free Mass, Power, and Maximum Hamstring Force in Female Basketball Athletes - Budijono, Agung Prijo; Siantoro, Gigih; Dhenabayu, Riska; Hartoto, Setiyo; Kusuma, Donny Ardy; Firmansyah, Awang; Prasetya, Muhammad Reza Aziz; Garcia-Jimenez, Jose V. (Physical Education Theory and Methodology, 2024)
Background. In competitive sports, especially basketball, physical attributes such as agility, speed, strength, and power are crucial for performance. Objectives. This study aimed to examine the correlation between fat-free mass (FFM), countermovement jump (CMJ) power, and maximum hamstring force in female basketball athletes, providing insights that could enhance performance and reduce injury risk. Materials and methods. This observational cross-sectional study investigates the relationship between fat-free mass (FFM), power, and maximum hamstring force in 45 female basketball athletes. The Anderson-Darling test for assessing normality and Spearman’s correlation for non-normally distributed data were used to conduct the study. Results. Significant correlations were found between FFM and maximum hamstring force in the both right (r = 0.585, p < 0.001) and left legs (r = 0.522, p < 0.001), as well as between (CMJ) power and maximum hamstring force for both legs (right: r = 0.467, p = 0.001; left: r = 0.434, p = 0.003). Additionally, power was significantly correlated with jump height (r = 0.604, p < 0.001). Conclusions. These findings suggest that FFM and power are critical determinants of hamstring strength and explosive performance in female basketball athletes.